Microbiological monitoring of the development of children with congenital heart disease - Filonenko, G. V.; Salamanina, A. A.; Kyryk, D. L. (Ukrainian Journal of Cardiovascular Surgery, 2017)
The analysis of the problem of postoperative bacterial infection allow to highlight aspects, of discussions which presently are of particular relevance and importance for high-tech cardiac surgery. Objective:To determine the incidence of bactere-mia and its etiological structure in infants with congenital heart disease (CHD). Methods. Microbiological, statistical analysis. Results. A comparative analysis of the results of bacteria logical stady of blood samples obtained from 218 infants were surgical treatment from 2015 to 2016y. It was ectablished that within the spectrum of pathogens of bacteremia in patients for 2015y Non-fermenting gram-negative microorganisms (43.1%), for 2016y – coagulase-negative staphycoccus (25.6%) was predominant. Conclusions. Infants with CHD should be included into the risk group for bacteremia and other postoperative IC. Microbiological monitoring is one of the major components of infection control in cardiac surgery hospitals providing science-based antibiotic therapy and IC prevention methods. Further research should focus on determining the molecular-genetic determinants of antibiotic resistance, especially beta-lactamase and carbapenemase.